Peningkatan Pengembangan Nilai Agama dan Moral Melalui Metode Teori Piaget - Dina, Dina; Jamila, Jamila; Juariyah, Juariyah; Yulianti, Silvia; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Instruction and habituation often lead young children to develop religious and moral principles "automatically." However, this method needs to be questioned when compared with a better understanding of how children's cognition functions. This article examines Piaget's theory of cognitive development as a basis for enhancing the internalization of moral and religious values. To conduct the analysis, we examine how stages of children's cognitive development, particularly the preoperational stage, relate to pedagogical strategies based on concrete experiences, exploratory activities, and social interactions. The results show that learning religious and moral values ​​through hands-on activities, simple reflective discussions, and role-playing produces more stable understandings than verbalistic approaches. This method not only teaches children what is right and wrong but also builds their self-confidence. The results demonstrate that Piaget's theory is a pedagogical necessity to make the process of internalizing values ​​more authentic and relevant for young children.